Beauty Centers - Toqa Abdo; Rand Motaz (My University, 2023)
Day by day, the development of life is increasing in various fields of life, and one of these areas is the field of programming and technology. Smart devices have become an integral part of our daily lives. Developing applications that facilitate our daily lives is crucial, especially considering how fast our lives have become. The project aims to facilitate the purchase of hair care and skin care products from more than one store, as the application brings together several stores and puts their products at the user’s fingertips. The application provides a variety of distinct services to users and store owners, and on the user’s side, the application shortens a lot of time for the user to visit more than one store and puts all the stores in front of him. It also shows him additional complementary options on the product he ordered. Also, after the user purchases the goods, the application issues a purchase invoice containing the products he purchased and the price of each product, which enables him later, in case of problems, to return and search for a specific invoice according to the date of its issue and match the incoming product with the product that was monitored in the invoice. The application provides the ability to chat between the store owner and the user. As for store owners, the application makes it easier for them to display their products and the possibility of competition among other stores. Also, the app sends a notification to the store owner if the quantity offered has expired or is about to expire. As well as conducting various statistics related to sales and others. There are not many applications similar to ours. However, there are apps similar to ours in some stores, but there is no app that brings more than one store together and provides chat and notification features. We developed and built this app using php and flutter.
TrainLink